Spillover Effects of Benchmark Companies Improved Environmental, Social, And Governance (ESG) Performance on Industry Customer Relationship Stability: Empirical Evidence from China - Li, Li; Shen , Qingyuan (Transformations In Business & Economics, 2026)
The uncertainty and dynamic complexity of the external environment have led to frequent and rapidly spreading supply chain disruptions. Improving. Environmental, Social, and Governance (ESG) ratings to stabilize supply chain customer relationships has gradually become a focal issue in business practice and theoretical research. However, existing literature lacks systematic theoretical insights into how improved ESG performance by industry benchmark firms enhances customer relationship stability. Drawing on signaling and dynamic competition theories, and using ESG rating data from Chinese A-share listed companies from 2013 to 2024, a fixed-effects model at the industry level was constructed to examine whether the industry spillover effect of benchmark firms’ improved ESG performance on customer relationship stability is positive or negative, and to analyze the underlying mechanism of this spillover effect. Results show that improved ESG performance by benchmark firms generates a positive industry spillover effect on customer relationship stability (0.1080). The mechanism involves benchmark firms driving industry-wide ESG rating improvements, thereby leading other firms to enhance product differentiation and strengthen corporate reputation to stabilize customer relationships. This positive spillover effect intensifies when firms perceive high external environmental uncertainty and possess strong dynamic capabilities. Furthermore, the positive spillover effect can lead to economic outcomes that reduce fluctuations in supply–demand volumes and relationships. The conclusions offer valuable insights for comprehensively advancing ESG implementation across industries, reinforcing the “chain leader” role of benchmark enterprises, stabilizing supply chain customer relationships, and balancing supply–demand dynamics.